Analisis Perbandingan Teknik Rendering Menggunakan Adobe Media Encoder Dan Software Adobe Premiere - Ali Sutan Pane; Agung kharisma Hidayah (UNIVED Press, 2022)
Abstract This study discusses the comparative analysis of rendering techniques using adobe media encoder and adobe premiere pro software with the aim of knowing the results of the rendering time of adobe media encoder cc 2018 and adobe premiere pro cc 2018 on cinematic video rendering and also knowing the level of video feasibility produced by adobe media encoder cc 2018 and adobe premiere pro cc 2018 on cinematic videos. In the research of Comparative Analysis of Rendering Techniques Using Adobe Media Encoder and Adobe Premiere Software, the author uses research and development research methods. Then for the methodology for the cinematic video